The Influence of Service Quality, Customer Value, Trust, on the Decision of Informal Workers to Become BPJS Employment Participants in Ceger, East Jakarta - Rian Hidayat; Resti Hardini; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to determine the effect of service quality, customer value, customer trust on the decision of informal workers to become participants in BPJS Employment in Ceger, East Jakarta. This study uses a purposive sampling technique with a total of 100 respondents, where there are sample characteristics of informal workers BPJS Ketenagakerjaan, Ceger Branch. Data analysis technique uses multiple linear regression analysis and uses the Statistical Product and Service Solution (SPSS) version 26.0 program. The results showed that service quality had a positive and significant effect on purchasing decisions, which can be seen from the t-test, where the value of tcount > ttable (2.198 > 1.988) and a significant value of 0.030 <0.05. Customer value has a positive and significant effect on purchasing decisions, it can be seen from the t-test, where the value of tcount> ttable (4.571> 1.988) and a significant value of 0.000 <0.05. Customer trust has a positive and significant effect on purchasing decisions can be seen from the t-test, where the value of tcount > ttable (5.341>1.988). Significant value of 0.000 < 0.05.